Aplikasi Ergonomic Function Deployment (EFD) pada Redesign Alat Parut Kelapa untuk Ibu Rumah Tangga - Roberta Zulfhi Surya; Rusdi Badruddin; M. Gasali (Jurnal Optimasi Sistem Industri, 2014)
Grate the coconut is one of kitchen activity which faces by housewife in daily life. A coconut grater product which is distibuted in market, one of them is manual crank system. Housewife complain that they feel painfull in their body, especially at hand. Waist and back after using available old tool. This research is purposed to improve the design of coconut grater with crank system by ergonomic function deployment (EFD) approach, also to known mosculuskletal reducing of housewife as user and show differention time of grater after redesign done. Research was conducted in RT. 001 RW.005 Tembilahan, Indragiri Hilir District. Research model used treatment by subject design with total sample is 12 housewife which is calculation by Colton Formula. Improvement new coconut grater design with crank system which EFD got by creat the matrix house of ergonomic (HOE) and determination of anthropometry data. Mosculuskletal complain on housewife is measured by making the Nordic Body Map (NBM) Questionnaire work sheet. Time of grated the coconut got by testing coconut grater by crank system on before and after using. Research finding after redesign of coconut grater of crank system shown that design of coconut grater of crank system with EFD and base on ergonomic acpects (effective, confort, savety, healthy and efficient. Mosculuskletal complaint that happend on housewife decrease about 0,285 or 17,39%. Time of grate is also faster around 5 minutes or has imporove 30,1%.